2008
DOI: 10.1007/s10620-008-0382-z
|View full text |Cite
|
Sign up to set email alerts
|

Transsulfuration Pathway Defects and Increased Glutathione Degradation in Severe Acute Pancreatitis

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Hence, methionine metabolism through the trans-sulfuration pathway and the trans-methylation system decisively contributes to the maintenance of redox homeostasis in cells [6]. Increased levels of homocysteine, a sign of dysregulation of the trans-sulfuration pathway, have been detected in plasma of patients with a variety of gastrointestinal disorders including inflammatory bowel disease [7,8], colorectal cancer [9] as well as acute pancreatitis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, methionine metabolism through the trans-sulfuration pathway and the trans-methylation system decisively contributes to the maintenance of redox homeostasis in cells [6]. Increased levels of homocysteine, a sign of dysregulation of the trans-sulfuration pathway, have been detected in plasma of patients with a variety of gastrointestinal disorders including inflammatory bowel disease [7,8], colorectal cancer [9] as well as acute pancreatitis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Transsulfuration impairment is also associated with other disorders such as autism [48], cirrhosis [913], coronary artery disease [1418], goiter [19], impaired coagulation [2022], immune function [23], neurodegenerative disease [2426], and pancreatitis [27]. This variety of afflictions highlights the importance of transsulfuration to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread nature of tissues involved in these disorders, our knowledge of transsulfuration is confined to the liver and a small number of other tissues. These include the brain [28], certain lymphoid cells [29], and the pancreas [27, 30]. …”
Section: Introductionmentioning
confidence: 99%
“…Abu-Zidan et al ( 42 ) demonstrated that OS markers are positively correlated with the severity of pancreatitis. In addition, AP is characterized by pancreatic glutathione depletion ( 50 , 51 ). Rahman et al ( 51 ) reported that decreased concentration of glutathione is associated with increased level of its metabolite cysteinyl glycine, which might induce severe AP.…”
Section: Antioxidants and Oxidative Stressmentioning
confidence: 99%